NAFKAH SUAMI FAKIR DALAM KONTEK KEKINIAN: (Kontribusi Mazhab Maliki) - Aziz, Nasaiy; Suheri (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2020)
Fuqha' agreed to stipulate that the husband's living responsibilities in the family are adjusted to his ability and also released taanggung his responsibilities due to his fact. They differed in their views around whether the living was used as a debt to be paid when he could afford it. This paper specifically aims to know the Maliki sect's view of the husband's living responsibilities and their consequences and their relevance to the consctice ofkenianness. The Maliki sect is of the view, the husband's living is lost and does not become a debt to be paid when he is able and a new judge may divorce them based on the wife's lawsuit because of his fact. The opinion of the Maliki sect tends to be appropriate and relevant to the current kontek. In the sense of living the husband of the poor does not have to be a debt and the reality of society today does not burden the husband of the poor to spend it and also does not make the utaang to be paid when the husband can afford.